Reactance and norms in a highly collectivist and compliance-oriented society - Alhugbani, Hessah Fahd (Frontiers in Communication, 2025)
The purpose of this study is to test the theories of communication about health crises and theories of persuasive health communication that have been applied to COVID-19 in a different cultural context in order to understand these theories need to be adapted for a global pandemic. In order to explore this realm, the conceptual framework established by the theory of planned behavior is expanded by adding two components. The first component is to understand the role of compliance and the way it interacts with psychological reactance. The second component is to understand the role of collectivism in the way it interacts with the subjective norms component of the integrated model. By utilizing message cues, this study used an experimental design to empirically test whether using the norms and compliance cues affect behavioral intentions to follow government-enforced health policies to contain COVID-19. A between-subjects experiment was conducted with random assignment to one of three conditions: a health message with language of compliance, a health message with a norm cue, and a control health message without either of these treatments. In order to test the hypotheses of this study, two samples were recruited. One was from King Saud University (KSU) students and the other sample was from University of Missouri (Mizzou) students. The results of this study led to conclude that cultural differences do exist, but the tools to theorize about these differences need to be developed and refined.